125-th anniversary of electrical engineering education and science in Lviv Polytechnic (1891–2016) - Стахів, Петро; Рендзіняк, Сергій; Гоголюк, Оксана; Stakhiv, Petro; Rendzinyak, Serhiy; Hoholyuk, Oksana (Lviv Politechnic Publishing House, 2017)
Подано історію заснування, розвитку та сьогодення кафедри торетичної та загальної електротехніки Національного університету “Львівська політехніка”. Висвітлено роль кафедри у становленні європейської електротехнічної науки, її основні досягнення та перспективи подальшого розвитку.

The article deals with the history of foundation, development and modern state of Department of Theoretical and General Electrical Engineering of Lviv Polytechnic National University. The role of the Department in the development of European electrical science, its main achievements and prospects of further development are discussed.
До 125-річчя електротехнічної освіти і наки у Львівській політехнці
Keywords: electrical engineering; anniversary; education process; history of science